Bioinformatics analysis of ferroptosis-related hub genes and immunoinfiltration in myocardial ischemia/reperfusion following heart transplantation - Yuxi Zhang; Qiao Tang; Jiahui Cui; Yanan Li; Heng Xu; Zhen Qiu; Shaoqing Lei; Rui Xue; Qian Sun; Zhongyuan Xia (BMC Cardiovascular Disorders)
Abstract Background Ischemia/reperfusion (I/R) is an inevitable pathophysiological process during heart transplantation, and ferroptosis is an important pathogenic mechanism. Unlike other modes of cell death, ferroptosis depends on the accumulation of iron within the cell and the oxidative degradation of polyunsaturated fatty acids. Dysregulation of this pathway has been linked to the progression of multiple pathological conditions, making it an attractive target for therapeutic intervention. Therefore, this study aims to explore the effect of ferroptosis on I/R during heart transplantation. Methods GEO2R was applied to identify differentially expressed genes (DEGs) obtained from GSE50884 data, which was involved in I/R and heart transplantation. And ferroptosis-related DEGs (FRDEGs) were screened by venn diagram with ferroptosis-related genes downloaded from FerDb database. FRDEGs was enriched and analyzed by GO and KEGG, and hub genes related to ferroptosis were screened by Cytoscape software and database STRING. Additionally, considering the relationship between ferroptosis and immunity, CIBERSORTx was to analyze the infiltration of 22 kinds of immune cells in I/R during heart transplantation, and the correlation between each immune cell and the expression of FRDEGs was also discussed. Finally, the mouse model of heart transplantation with I/R was constructed, and the hub genes was verified by RT-qPCR and western blot. Results 12 FRDEGs were identified out of 327 DEGs in GSE50844, which were mainly involved in ferroptosis and other pathways. Three hub genes (SLC7A11, PSAT1, ASNS) were obtained by the degree algorithm of cytohubba plug-in. Immunoinfiltration analysis showed that 16 of 22 immune cells changed, and the immune score of heart transplantation with I/R was higher than that without I/R. In addition, hub genes exhibited significant correlation with Eosinophils, NK cells resting, Dendritic cells resting, NK cells activated and T cells CD4 memory activated. We verified the expression of SLC7A11, PSAT1 and ASNS was higher than that in normal tissues using RT-qPCR and western blot in mouse models of heart transplantation with I/R, companied by ferroptosis aggravated is involved. Conclusions In short, ferroptosis is involved in I/R injury during heart transplantation, which is related to immune cell infiltration. Three hub genes (SLC7A11, PSAT1 and ASNS) identified in this study provide therapeutic targets for ameliorating I/R injury in heart transplantation.